Immunohistochemical Profile of Er, Pr, Her2, and Ki-67 In Breast Cancer Patients - Marliana Nurprilinda; Erida Manalu; Tiroy Sari B. Simanjuntak; Reinhard Christovel Andreas (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Breast cancer remains one of the leading causes of cancer-related mortality among women worldwide, with hormonal factors playing a critical role in tumor development and progression. This study aims to describe the immunohistochemical profile of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki-67 in breast cancer patients at MRCCC Siloam Semanggi Hospital in 2022. A retrospective descriptive study was conducted using a total sampling of anatomical pathology archives, comprising 316 breast cancer cases. The most common age group was 40-49 years. ER positivity was observed in 229 patients (72.5%), while PR positivity was found in 183 patients (57.9%). HER2 overexpression (3+) was identified in 75 patients (23.7%); cases with equivocal HER2 (2+) required confirmation by in situ hybridization. High proliferative activity, indicated by Ki-67 ≥20%, was present in 262 patients (82.9%). These findings indicate a predominance of hormone receptor-positive tumors with high proliferative indices, highlighting the importance of immunohistochemical profiling in guiding prognosis assessment, therapeutic decision-making, and selection of targeted and systemic treatments in breast cancer management. Keywords: Breast Cancer, Immunohistochemistry, Estrogen Receptor (ER), HER2, Ki-67